Perancangan Board Game Sebagai Media Untuk Melestarikan Kue Tradisional Nusantara Kepada Anak-Anak - Grasella Davina Audria; Irwan Harnoko; Nugroho Widya Prio Utomo (STIKes Ibnu Sina Ajibarang, 2024)
Indonesia has a variety of traditional Nusantara cakes that are not only unique, but also appetizing. However, along with the development of the times, traditional Nusantara cakes are increasingly rare. Only a handful of sellers are still loyal to selling these snacks. One of the reasons for the decline in the popularity of these traditional cakes is the growing perception among the public, especially children, who consider these cakes